The Clinicopathological Profile and Recurrence of Meningioma at Department of Anatomical Pathology, Faculty of Medicine, Universitas Indonesia/Dr. Cipto Mangunkusumo Hospital - Hastrina Mailani; Susanto, Eka (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2024)
Background Meningioma represents the most frequent primary intracranial tumor, and some subtypes may demonstrate aggressive characteristics with a correspondingly elevated risk of recurrence. To predict the likelihood of recurrence, clinical and pathological parameters are essential. More aggressive treatment strategies and strict follow-up can be implemented using these parameters. Therefore, this study aims to determine clinicopathological characteristics of meningioma and its relationship with recurrence. Method This study adopted a retrospective cross-sectional approach using secondary data of meningioma cases from the archives of the Department of Anatomical Pathology, Faculty of Medicine, Universitas Indonesia/Dr. Cipto Mangunkusumo Hospital in 2019-2021. The clinical data were obtained through electronic medical records, and histopathological data assessment, including grade, mitosis, brain invasion, bone invasion, and dural invasion, was conducted through microscopic examination. Result The data indicate that a total of 219 cases of meningioma were reassessed. The mean age of patients was 45±11 years, and the majority (88.1%) were female. The mean tumor size was 5±1.8 cm, with the most common tumor location being the skull base (71%) and 38.6% of cases showed radiological evidence of bone invasion. Subtotal resection was the treatment of choice for most patients (67.8%). CNS WHO grade 1 was found in 91.8% of cases, while Mitotic index ≥4/10 HPF, microscopic evidence of bone invasion, brain invasion, and dural invasion were found in 5%, 33.6%, 3.2%, and 16.8%, respectively. A minimum follow-up of 6 months was fulfilled by 71 cases, and 28% experienced recurrence/progression. These findings showed a significant association between the extent of resection (p=0.007) and tumor size (p=0.02) with the incidence of recurrence. Conclusion Clinical parameters such as the extent of resection and tumor size play a role in predicting the likelihood of meningioma recurrence. The predictive factors knowledge for meningioma recurrence is important in determining treatment strategies and follow-up